Immigration And Tuberculosis In A Brazilian Border State: Epidemiological Characterization Of Cases Among Venezuelan Immigrants In The State Of Roraima, Brazil - Benedetti, Maria Soledade Garcia; Capistrano, Émerson Ricardo de Sousa; Oliveira, Angela Maria Félix Alves; Lamounier, Elba Urzedo de Freitas; Rocha, Karla Cristina Souza; Alves, Maria Gorete Sousa (Seven Editora, 2023)
Objective: To describe the epidemiological characteristics of tuberculosis among Venezuelan immigrants in the state of Roraima, Brazil. Methods: A descriptive and retrospective study, data were collected from the Information System of Notifiable Diseases - Sinan, in the period from 2012 to 2021. The sociodemographic variables were analyzed: gender, age group, skin color/race, education (by education level), municipality of residence, social situation (population deprived of freedom and homeless population), and clinical: clinical form, type of entry, case closure and comorbidities. The data were organized and analyzed in the Excel Program®  and a descriptive analysis of the absolute and percentage frequency of the variables was performed. Results: 347 cases of tuberculosis occurred among Venezuelan immigrants, representing 14.7% of the total cases of the disease reported in the state in the study period. There was a predominance of cases among males (66.3%), 30 to 59 years of age (36.5%), and brown skin color (65.7%). As for the clinic: new cases (88.5%), pulmonary form (82.7%), co-infection with HIV/AIDS (22.1%), cure (44.7%), abandonment (19.6%) and death (8.0%). Conclusion: The detection of cases of tuberculosis among immigrants has increased in recent years, which may be due to their conditions of vulnerability, and therefore, it is essential to adopt strategies to expand access to early diagnosis and treatment for this population, in order to avoid complications and the spread of the disease. DOI: https://doi.org/10.56238/colleinternhealthscienv1-111